Tolerance of lonkida (Nauclea orientalis L.) seedlings inoculated with mycorrhizae against drought and waterlogging stress - Faisal Danu Tuheteru; Asrianti Arif; Husna Husna; Basrudin Basrudin; Albasri Albasri; Irdika Mansur; Maman Turjaman; Miranda Hadiyanti Hadijah; Agnitje Rumambi; Budi Prasetya; Armila R Male (Journal of Degraded and Mining Lands Management, 2022)
Abiotic stress is a limiting factor for plant growth and development. The use of arbuscular mycorrhizal fungi can reduce the negative effects of abiotic stress. This study aimed to determine the tolerance of Nauclea orientalis inoculated with mycorrhizae to drought and waterlogging stresses. This research was carried out at the Indonesian Mycorrhizal Association’s greenhouse and Forestry laboratory University of Halu Oleo in Kendari City, Southeast Sulawesi Province, Indonesia, from March to June 2019. The study used a factorial completely randomized design consisting of two factors. The first factor was Arbuscular Mycorrhizal Fungi (AMF) inoculations (A) consisting of a control, AMF types of Acaulospora sp.-1, and Claroideoglomus etunicatum.  The secod factor was environmental stress treatments (B) consisting of a control, soil moisture 25% of field capacity, 50% of field capacity, inundated as high the polybag (9 cm high) and inundated over the polybag. The results showed that local AMF was effective in improving plant growth. Interaction between inoculation of Acaulospora sp.-1 and environmental stress significantly increased AMF colonization on the N. orientalis roots. Inoculation of C.etunicatum significantly improved the N. orientalis growth. The treatment of drought stress with a field of 50% field capacity negatively influenced plant dry weight and the relative growth of the N. orientalis.